Career Impact of the Double-reduction Policy on Out-of-school Counselling Teachers - Zhang, Shuting (Transactions on Social Science, Education and Humanities Research, 2024)
Since the implementation of the double-reduction policy, extracurricular tutoring teachers have faced many challenges. Through interviews with extracurricular tutoring teachers from New Oriental, this article provides insight into the current development of some extracurricular tutoring teachers, as well as relevant analyses and outlooks. The article will explore the impact of the double-reduction policy on extracurricular tutoring teachers and the challenges teachers face in adapting to the new policy. At the same time, the article will also focus on the future career trends of extracurricular tutoring teachers and how they cope with the changing educational environment. Through this study, readers will gain a better understanding of the impact of the double-reduction policy on extracurricular tutors. Through this study, readers will gain a deeper understanding of the impact of the double-decrease policy on extracurricular tutoring teachers. While this policy has resulted in the loss of job opportunities for some teachers, it has also provided new career paths for young teachers.